CD8+ T cell responses to human immunodeficiency viruses type 2 (HIV-2) and type 1 (HIV-1) gag proteins are distinguishable by magnitude and breadth but not cellular phenotype - Gillespie, G; Pinheiro, S; Sayeid-Al-Jamee, M; Alabi, A; Kaye, S; Sarge-Njie, R; Njai, H; Joof, K; Jaye, A; Whittle, H; Rowland-Jones, S; Dorrell, L (2005)
The mechanisms underlying the relatively slow progression of human immunodeficiency virus type 2 (HIV-2) compared with HIV-1 infection are undefined and could be a result of more effective immune responses. We used HIV-2 and HIV-1 IFN-γ enzyme-linked immunospot assays to evaluate CD8+ T cell responses in antiretroviral-naive HIV-2-('HIV-2+') and HIV-1-infected ('HIV-1+') individuals. Gag-specific responses were detected in the majority of HIV-2+ and HIV-1+ subjects. Overlapping gag peptide analysis indicated a significantly greater magnitude and breadth of responses in the HIV-1+ cohort, and this difference was attributable to low responses in HIV-2+ subjects with undetectable viral load (medians 2107 and 512 spot-forming units per 106 PBMC, respectively, p=0.007). We investigated the phenotype of viral epitope-specific CD8+ T cells identified with HLA-B53- and HLA-B58-peptide tetramers (8 HIV-2+, 11 HIV-1+ subjects). HIV-2-specific CD8+ T cells were predominantly CD27+ CD45RA-, and only a minority expressed perforin. The limited breadth and low frequency of CD8+ T cell responses to HIV-2 gag in aviremic HIV-2+ subjects suggests that these responses reflect antigen load in plasma, as is the case in HIV-1 infection. Immune control of HIV-2 does not appear to be related to the frequency of perforin-expressing virus-specific CD8+ T cells. © 2005 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.